A novel form of perceptual attunement: Context-dependent perception of a native contrast in 14-month-old infants. (August 2017) - Fort, Mathilde; Brusini, Perrine; Carbajal, M. Julia; Sun, Yue; Peperkamp, Sharon
Graphical abstract: Highlights: A novel form of infants' perceptual attunement to a native contrast is shown. An original Type I error-free EEG Mismatch paradigm is used in 14-month-olds. Like adults, infants do not detect a native voicing contrast in specific contexts. Infants' perceptual attunement to their native language is context-dependent. Abstract: By the end of their first year of life, infants have become experts in discriminating the sounds of their native language, while they have lost the ability to discriminate non-native contrasts. This type of phonetic learning is referred to as perceptual attunement. In the present study, we investigated the emergence of a context-dependent form of perceptual attunement in infancy. Indeed, some native contrasts are not discriminated in certain phonological contexts by adults, due to the presence of a language-specific process that neutralizes the contrasts in those contexts. We used a mismatch design and recorded high-density Electroencephalography (EEG) in French-learning 14-month-olds. Our results show that similarly to French adults, infants fail to discriminate a native voicing contrast (e.g., [f] vs. [v]) when it occurs in a specific phonological context (e.g. [ofbe] vs. [ovbe], no mismatch response), while they successfully detected it in other phonological contexts (e.g., [ofne] vs. [ovne], mismatch response). The present results demonstrate for the first time that by the age of 14 months, infants' phonetic learning does not only rely on the processing of individual sounds, but also takes into account in a language-specific manner the phonological contexts in which these sounds occur.